Identifying reproducible individual differences in childhood functional brain networks: An ABCD study. (December 2019) - Marek, Scott; Tervo-Clemmens, Brenden; Nielsen, Ashley N.; Wheelock, Muriah D.; Miller, Ryland L.; Laumann, Timothy O.; Earl, Eric; Foran, William W.; Cordova, Michaela; Doyle, Olivia; Perrone, Anders; Miranda-Dominguez, Oscar; et al.
Abstract: The 21-site Adolescent Brain Cognitive Development (ABCD) study provides an unparalleled opportunity to characterize functional brain development via resting-state functional connectivity (RSFC) and to quantify relationships between RSFC and behavior. This multi-site data set includes potentially confounding sources of variance, such as differences between data collection sites and/or scanner manufacturers, in addition to those inherent to RSFC (e.g., head motion). The ABCD project provides a framework for characterizing and reproducing RSFC and RSFC-behavior associations, while quantifying the extent to which sources of variability bias RSFC estimates. We quantified RSFC and functional network architecture in 2, 188 9-10-year old children from the ABCD study, segregated into demographically-matched discovery (N = 1, 166) and replication datasets (N = 1, 022). We found RSFC and network architecture to be highly reproducible across children. We did not observe strong effects of site; however, scanner manufacturer effects were large, reproducible, and followed a "short-to-long" association with distance between regions. Accounting for potential confounding variables, we replicated that RSFC between several higher-order networks was related to general cognition. In sum, we provide a framework for how to characterize RSFC-behavior relationships in a rigorous and reproducible manner using the ABCD dataset and other large multi-site projects.